School bullying and its connection with social skills of the second circle students of essential education in salamieh city. (Journal of Hama University, 2019)
The research aimed to determine the degree of spread of the school bullying phenomenon between the individuals of the research sample, and studying the relation between school bullying and social skills, and discovering the differences between the answers of the individuals of the research sample on the scale of school bullying and social skills according to the variable of ( gender ), and discovering the differences between the answers of the individuals of the research sample ( bullying – non bullying) on the scale of social skills, the researcher depended on the analysis descriptive method, and the research sample reached (150) student both males and females of the (seventh- eighth – ninth) grade, and used the school bullying scale and social skills scale and she reached the following results:- the spreading degree of the school bullying phenomenon between the secondary phase students was medium.- there is a negative relation of statistic meaning at the indication level (0.5) between the students degrees on the school bullying scale and their degrees on the social behavior scale.- there are differences of statistic meaning between the medium of male and female students degrees on the school bullying scale according to the gender variable (male – female) in favor of males.- There are no differences of statistic meaning between the mediums of students degrees on the scale of social skills according to the gender variable (male – female).- there are differences of statistic meaning between the mediums of bullying and non-bullying students on the scale of social skills in favor of non-bullying students.